Factor by grouping: 16x³ +28x² - 28x - 49 = 0 is (4x² - 7) (4x - 7) = 0
Large polynomials can be divided into groups based on a common factor. As a result, we may factor each distinct group and then merge like words. We refer to this as factoring by grouping.
We have the equation,
16x³ +28x² - 28x - 49 = 0
In order to solve the equation by using factor by grouping:
We find common terms in between,
So, we arrange the terms,
16x³ +28x² - 28x - 49 = 0
4x² (4x - 7) -7 (4x - 7) = 0
Here, we have common term (4x-7).
Factor out the common binomial.
(4x² - 7) (4x - 7) = 0
Therefore, (4x² - 7) (4x - 7) = 0 is the factor.
To learn more about the factoring by grouping;
https://brainly.com/question/11919488
#SPJ1